AN ANALYSIS OF SOCIETIES, SPEAKERS AND TYPES OF LANGUAGES IN THE QURÁN - Sanat Md. Nasir (Proceedings Education and Language International Conference, 2017)
The paper is aimed at providing an analysis of societies, speakers and types of languages found in the Qurán. As with the speakers and types of languages, they are based on all the utterances in inverted commas found in the Malay translations of the Qurán. The concepts of societies analysed are verified from the textual and co-textual reading of the Qurán. The types of speakers and languages are listed statistically so as to be able to determine the inclinations. Discussions on the three concepts are made available by the findings of the analysis. The study hopes to give a better understanding and insights about the great book, i.e. the Qurán pertaining to such concepts. Keywords: societies, types of languages, speakers